Utilization of GPT-4 to Improve Education Quality Through Personalized Learning for Generation Z in Indonesia - Muhammad Fatihul Firdaus; Joseph Nugraha Wibawa; Fajri Fathur Rahman (President University, 2023)
The Golden Generation or Generation Z, an important part of the 2020-2035 demographic bonus, will face unique educational challenges, such as low literacy rates and uneven access to technology across regions[1]. To support the potential implementation of personalized learning for Generation Z in Indonesia, a research study was conducted to investigate the potential use of GPT-4, an artificial intelligence that uses the GPT language model and the latest Natural Language Processing (NLP) technology. Quantitative, qualitative, and literature study research methods were used to evaluate the effectiveness and accuracy of GPT-4 in the Indonesian educational context. Data was collected from sample testing and reference to previous GPT-4 research, and results were analyzed using predefined evaluation methods. The results of the analysis showed that there was an improvement in terms of coherence and knowledge with the GPT-4 model compared to previous models. To maximize the potential of GPT-4 in education, there needs to be strong support from various parties, as well as efficient adaptation to the specific needs of students and the educational environment in Indonesia [2]. With an integrated approach, ethics, and safety, GPT-4 has the potential to support inclusive and effective education for Generation Z in Indonesia.